2021
DOI: 10.3389/fnagi.2021.798297
|View full text |Cite
|
Sign up to set email alerts
|

Exercise Reduces H3K9me3 and Regulates Brain Derived Neurotrophic Factor and GABRA2 in an Age Dependent Manner

Abstract: Exercise improves cognition in the aging brain and is a key regulator of neuronal plasticity genes such as BDNF. However, the mechanism by which exercise modifies gene expression continues to be explored. The repressive histone modification H3K9me3 has been shown to impair cognition, reduce synaptic density and decrease BDNF in aged but not young mice. Treatment with ETP69, a selective inhibitor of H3K9me3’s catalyzing enzyme (SUV39H1), restores synapses, BDNF and cognitive performance. GABA receptor expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 48 publications
(91 reference statements)
1
5
0
Order By: Relevance
“…To support our findings, it was previously reported that the enhanced H3K4me2 in the Bdnf promoter of the lateral-medial hypothalamic forebrain bundle leads to Bdnf overexpression . Ionescu-Tucker et al also found that the reduced H3K9me3 in the brain is one of the reasons for BDNF activation . Therefore, we propose that arsenic exposure impaired learning and memory ability by inhibiting key gene expressions, which were attributable to the repressed H3K4 methylation and acetylation and the enhanced H3K9 methylation in rat hippocampus.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…To support our findings, it was previously reported that the enhanced H3K4me2 in the Bdnf promoter of the lateral-medial hypothalamic forebrain bundle leads to Bdnf overexpression . Ionescu-Tucker et al also found that the reduced H3K9me3 in the brain is one of the reasons for BDNF activation . Therefore, we propose that arsenic exposure impaired learning and memory ability by inhibiting key gene expressions, which were attributable to the repressed H3K4 methylation and acetylation and the enhanced H3K9 methylation in rat hippocampus.…”
Section: Discussionsupporting
confidence: 87%
“…39 Ionescu-Tucker et al also found that the reduced H3K9me3 in the brain is one of the reasons for BDNF activation. 40 Therefore, we propose that arsenic exposure impaired learning and memory ability by inhibiting key gene expressions, which were attributable to the repressed H3K4 methylation and acetylation and the enhanced H3K9 methylation in rat hippocampus.…”
Section: ■ Discussionmentioning
confidence: 92%
“…KEGG pathway analysis was found that GABRB2 was upregulated whereas GABRA2 was downregulated, which was verified by IHC of hippocampus between young and aging mice. Previous studies also demonstrated that GABRA2 expression decreased with age in the hippocampus ( 9 , 10 ). However, aging-related disorders on GABRB2 expression are contradictory.…”
Section: Discussionmentioning
confidence: 62%
“…Generally, GABA exerts its effects on nerves mainly through its receptors; GABRA2 (GABAA receptor subunit alpha2) and GABRB2 (GABAA receptor subunit beta2) are the two important subunits of GABAA receptor, respectively. Previous studies demonstrated that GABRA2 expression decreased with age in the hippocampus ( 9 , 10 ). However, aging-related disorders on GABRB2 expression are contradictory and need further experimental validation.…”
Section: Introductionmentioning
confidence: 92%
“…81 For example, exercise decreased the repressive histone modification H3K9me3 at a BDNF promoter, leading to an increase in BDNF in aged mice. 82…”
Section: Exercise-derived Myokines and Muscle-brain Crosstalkmentioning
confidence: 99%